The hajj from Malaysia: its history, management and impact on the Malay society, 1975-2005 - Ismail, Sharifah; Islam, Arshad (IIUM Press, 2017)
The objective of this book is to give a descriptive analysis of the Hajj institution in Malaysia, its history, management and impact on the Malay society during the period that extends from 1975 to 2005. During this time, the conduct of the Hajj from Malaysia to the holy places in the Kingdom of Saudi Arabia (KSA) had witnessed a series of development that are associated with the pilgrims, pilgrimage and Hajj management. The present book attempts to analyze these developments from four different perspectives. Firstly, it examines the history and development of the conduct of the Hajj from Malaysia to the holy lands since the pre-independence era to 2005. Secondly, it highlights the series of developments in the vision, mission and administration of the Malaysian pilgrimage organizer, Lembaga Tabung Haji (LTH or Tabung Haji) for a period of 30 years. Thirdly, it investigates the elements which have influenced the development of the Hajj institution in Malaysia during the stated period. Fourth, it examines the significance of Hajj for the Malay Muslims and its impact on various aspects of their lives. The writers adopt a qualitative method that enables her to analyze and assess the material and information collected from the primary and secondary sources, interviews and personal observations. Four conclusions are derived from this book. Firstly, the Hajj institution in Malaysia (1975 to 2005) had witnessed a series of development and progress. This period also marked a new transition era of the Hajj institution in Malaysia into a more organized and modern Hajj institution under the administration of Tabung Haji. Second, Tabung Haji had achieved its vision and mission of establishment both in financial and Hajj administrations. It has been phenomenally successful in building its reputation as one of the strongest Islamic financial institutions, owned and managed by the Muslims and pioneers in the field of modern Hajj management in the world. Third, major reforms initiated by the governments of Malaysia and KSA and the roles of Tabung Haji had considerably contributed to the significant changes in Malaysian Hajj management.